Potential contribution of Lablab residues to maize production in moist savanna of West Africa - Ewansiha, S.U.; Tarawali, Shirley A.; Odunze, A.C.; Iwuafor, E.N.O. (Informa UK Limited, 2008)
Soils of the moist savanna of West Africa are poor in nitrogen; the natural fallow regeneration time has shortened; fertilizer costs and scarcity makes nitrogen (N) fertilizer input inadequate; and crop yields are low. In the region, lablab (Lablab purpureus L., sweet also known as Dolichos lablab L.) has the potential to improve soil quality, provide food, and supply feed simultaneously. In this context, response of maize to N following natural fallow or lablab fallow was investigated in the northern Guinea savanna of Nigeria. Lablab plots were maintained for 2 years—first planted in 2000 and replanted in 2001. In 2001, at the beginning of the growing season and before planting, lablab residues on the plots from 2000 planting were incorporated. In 2002, prior to maize planting, lablab residues on the plots from 2001 planting were also incorporated. Similarly, vegetation on the fallow plots was incorporated. The natural fallow and six lablab accessions of different maturity group formed the main plots with 0 and 60 kg/ha N as subplots in a split plot design with three replicates. Maize (Oba Super 1) in lablab plots grew taller and produced more stover and grain yields than natural fallow. With 0 kg/ha N, maize grain yield from lablab plots was 6.0 t/ha, 57% higher than from natural fallow. Where 60 kg/ha N was applied, maize mean grain yield from lablab plots was 6.6 t/ha, 31% more than from natural fallow plot. Thus, adding N fertilizer to plots formerly grown to lablab enhanced the productivity of subsequent maize. The study showed that late maturing lablab would contribute more to maize production than early maturing lablab when lablab residues are incorporated; without N fertilizer input it would be possible to obtain up to the potential yield of maize with incorporated lablab residues.